Strategi Komunikasi Pemasaran Dalam Meningkatkan Penjualan Jasa Dekorasi Event Pada Masa Pandemi COVID-19 Di CV. Nata Florist Bali - Aristya, Ni Made Wulan; Arjaya, Ketut; Citrawati, Luh Putu (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
The purpose of this study is to determine an effective marketing communication strategy to increase sales of event decoration services in CV. Nata Florist Bali during the Covid-19 pandemic. The type of research used is descriptive qualitative. Sources of data obtained by using the instrument interview, observation, and documentation. Based on the results of data analysis found six effective marketing communication strategies used by CV. Nata Florist Bali to increase sales of event decoration services during the Covid-19 pandemic. The strategies are (1) sales promotion to become a marketing communication tool with the largest contribution through special prices for a certain period so that there will be an increase in revenue by 9% in 2021 (2) events and experiences by giving sponsorship to tenant events (3) word-of-mouth marketing by distributing consumer testimonials to social media (4) public relations by making donations to community organizations (5) interactive marketing using Instagram and Facebook (6) direct marketing by via whatsapp and e-mail. While there are two less effective strategies, namely advertising (advertising) is not carried out due to cost factors and personal selling is not carried out due to lack of human resources.